PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA - I Ketut Suparya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study aims (1) to improve the activity of learning mathematics through the application of the Cooperative learning model type TAI (Team Assisted-Individualization) grade IV students of SDN 4 Abiansemal Dauh Yeh Cani and (2) to improve mathematics learning outcomes through the application of TAI type Cooperative learning models (Team Assisted- Individualization) fourth grade students of SDN 4 Abiansemal Dauh Yeh Cani. This research is a classroom action research conducted in two cycles. The subjects of this study were 14th grade students of SDN 4 Abiansemal Dauh Yeh Cani in the 2018/2019 school year as many as 14 people. Data collection in this study was done by the method of (1) observation and (2) tests. The observation method is used to measure the activity of learning mathematics. The test method is used to measure mathematics learning outcomes. Data obtained from the method of observation and tests were then analyzed by quantitative descriptive analysis method. The results showed an increase in mathematics learning activeness after the application of the TAI (Team Assisted- Individualization) cooperative learning model, with the average percentage of mathematics learning activeness in cycle I of 68.23% being in the criteria of being quite active, and in cycle II the percentage of the average learning activeness mathematics to 80.83% is in active criteria. Likewise with mathematics learning outcomes has increased with the average percentage of mathematics learning outcomes in the first cycle of 68.9% is in the criteria sufficient with classical completeness 64.28% and in the second cycle the average percentage of mathematics learning outcomes to 77.5% is at good criteria with classical completeness 85.71. In this class action research, it shows that there has been an increase in the activeness and learning outcomes of mathematics after applying the type of cooperative learning model TAI (Team Asissted- Individualization).